DESAIN E-LEARNING UNTUK MODEL PEMBELAJARAN DENGAN PENGENDALIAN UMPAN BALIK - , DWIJOKO PURBOHADI; , Ir. Lukito Edi Nugroho, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
An ideal learning can be achieved if it is held by one lecturer for one student, have sufficient time, is supported by adequate facilities, and uses appropriate ways. In this kind of condition, most students will achieve mastery because the lecturer will comprehend what he should do when a student has difficulty (it is said that learning has effect size 2.0). Nowadays, lecturer handles too many students so that there is a limitation in giving proper attention and treatment. As a result, the student's chance to achieve mastery is getting narrower. Many learning methods have been created to increase the effect size in order to achieve ideal learning